(untitled) (Anwer Khan Modern Medical College Journal, 2019)
Chromobacterium violaceum is isolated from soil and water in tropical and subtropical areas. This Gram negative, capsulated, motile bacillus is considered as a saprophyte but occasionally it can act as an opportunistic pathogen for animals and human. It causes skin lesion with liver and lung abscesses, pneumonia, gastrointestinal tract infections, urinary tract infections, osteomyelitis, meningitis, peritonitis, endocarditis, respiratory distress syndrome and septic shock. Increasing reported cases with Chrombacterium violaceum infection has been noticed in recent decades. It should be considered for its difficult-to-treat entity characterized by a high frequency of sepsis, distantant metastasis, multidrug resistance and relapse. High mortality rate associated with this infection necessitate prompt diagnosis and appropriate antimicrobial therapy Anwer Khan Modern Medical College Journal Vol. 10, No. 2: July 2019, P 169-175